The Soviet Century : Archaeology of a Lost World - Schlögel, Karl (Book collections on Project MUSE., 2023)
"The Soviet Union is gone, but its ghostly traces remain, not least int he material vestiges left behind in its turbulent wake. What was it really like to live in the USSR? What did it look. fell smell, and sound like? In The Soviet Century, Karl Schlögel, one of the world's leading historians of the Soviet Union, presents a spellbinding epic that brings to life the everyday world of a unique lost civilization. A museum of--and travel guide to--the Soviet past, The Soviet Century explores i evocative detail both the largest and smallest aspects of life int he USSR, from the Gulag, the planned economy, the railway system, and the steel city of Magnitogorsk to cookbooks, military medals, prison camp tattoos, and the ubiquitous perfume Red Moscow. The book examines iconic aspects of Soviet life, including long queues outside shops, cramps communal apartments, parades, and the Lenin mausoleum, as well as less famous but important parts of the USSR, including the Great Soviet Encyclopedia, the voice of Radio Moscow, graffiti, and even the typical toilet, which became a pervasive social and cultural topic. Throughout, the book shows how Soviet life simultaneously combined utopian fantasies, humdrum routine, and a pervasive terror symbolized by the Lubyanka, then as now the headquarters of the secret police. Drawing on Schlögel's decades of travel in the Soviet and post-Soviet world, and featuring more than 8- illustrations, The Soviet Century is vivid, immediate, and grounded in firsthand encounters with the places and objects it describes. The result in an unforgettable account of the Soviet Century.